2017
DOI: 10.1136/tobaccocontrol-2016-053476
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a complex healthcare intervention to increase smoking cessation in pregnant women: interrupted time series analysis with economic evaluation

Abstract: ObjectivesTo evaluate the effectiveness of a complex intervention to improve referral and treatment of pregnant smokers in routine practice, and to assess the incremental costs to the National Health Service (NHS) per additional woman quitting smoking.DesignInterrupted time series analysis of routine data before and after introducing the intervention, within-study economic evaluation.SettingEight acute NHS hospital trusts and 12 local authority areas in North East England.Participants37 726 records of singleto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
76
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(80 citation statements)
references
References 23 publications
4
76
0
Order By: Relevance
“…Some pregnant smokers with experience of an opt‐out referral have reported being unhappy with the lack of choice with some even describing powerlessness and resentment (Sloan et al ., 2016). Yet opt‐out pathways have been shown to increase support, access, and abstinence (Bell et al ., 2017; Campbell et al ., 2017). Informing health care professionals of the potential benefits of opt‐out over opt‐in referrals, including emphasizing that many pre‐implementation concerns do not emerge post‐implementation (Campbell et al ., 2016), could help with adoption and delivery (Jordan et al ., 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some pregnant smokers with experience of an opt‐out referral have reported being unhappy with the lack of choice with some even describing powerlessness and resentment (Sloan et al ., 2016). Yet opt‐out pathways have been shown to increase support, access, and abstinence (Bell et al ., 2017; Campbell et al ., 2017). Informing health care professionals of the potential benefits of opt‐out over opt‐in referrals, including emphasizing that many pre‐implementation concerns do not emerge post‐implementation (Campbell et al ., 2016), could help with adoption and delivery (Jordan et al ., 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Integrating agreed scripts to aid discussion around smoking could help professionals present a clear and comprehensive picture of the risks and avoid the common practice of raising only certain risks to minimize upset, which is largely at odds with the information preferences of pregnant smokers (Arborelius & Nyberg, 1997; Lendahls et al ., 2002). Health care professionals have reported interest in scripts for discussing smoking with pregnant women (Colomar et al ., 2015), and a midwife‐delivered standardized ‘risk perception’ intervention has already been implemented in North East England as part of an opt‐out referral pathway (‘BabyClear’) (Bell et al ., 2017). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By the use of this approach the establishment of Federal Road Safety Corps in Nigeria has been shown to have the impact of reducing the number of accidents on Nigerian roads temporarily by Oreko et al [6]. Bell et al [7] evaluated the impact of healthcare intervention on the smoking habits of some pregnant women and observed that it produced the expected effect of increased quitting of the habit by the pregnant women on delivery. Etuk and Victor-Edema [8] proposed an intervention model for monthly Naira/Euro exchange rates.…”
Section: Introductionmentioning
confidence: 99%
“…CONCLUSIONS It may be concluded that PMS distribution has been significantly affected by the deregulation of the downstream sector of the Nigerian crude oil industry. An adequate intervention model in this respect is given by equation (7). This might be used to explain and control this phenomenon.…”
mentioning
confidence: 99%